Diagnosing Ercoe’s Organizational Culture and Indicating Members’ Preferred Culture - Beyene, Tadesse (Journal of Asian Business Strategy, 2011)
This research examined at diagnosing the existing and preferred organizational culture of the Eritrean Center for Organizational Excellence (Ercoe) and indicated the cultural practice that fits to implement its strategic plan. Organizational culture is a commonly held in-the-mind of organizational members. It’s reflected by basic assumptions, rituals and values. These will be the basis how to perceive, think, feel, behave and expect others to behave in the organization. The target population for the survey comprised of Ercoe’s full time experts working as management trainers and consultants. The organizational culture of Ercoe was measured using personal interview of the management team by Organizational Culture Assessment Instrument (OCAI) developed by Quinn (1998). The research indicated that the existing organizational culture of Ercoe lied on the clan (collaborate culture) with 40.1 average followed by 23.8 for adhocracy (create culture). Also members’ preferred organizational culture was found to be the clan and adhocracy by 36.7 and 30.2 averages respectively. In order to attract the private sector, Ercoe should work hard towards its goal- to enhance market share locally and to penetrate in regional and international markets.